Semi-field evaluation of the bio-efficacy of two different deltamethrin formulations against Aedes species in an outdoor residual spraying study - Ab Hamid, Nurulhusna (Heliyon, 2020)
In recent decades, dengue incidence has trended upward worldwide causing urgent needs for new or modified vector control methods. We modified the existing indoor residual spraying (IRS) method by applying insecticide on the outer walls of building structures in an outdoor residual spraying (ORS) study. A semi-field study was conducted to investigate the bio-efficacy of two different deltamethrin formulations: K-Othrine® Polyzone, new polymer-enhanced deltamethrin formulated as a suspension concentrate (SC-PE), and K-Othrine® WG 250, traditional deltamethrin formulated as water dispersible granule (WG). The residual bio-efficacy of deltamethrin SC-PE was compared to deltamethrin WG on finished cement surfaces applied to the outer walls at the Institute for Medical Research (IMR), Malaysia. Standard WHO cone wall bioassays were adapted to evaluate the effective duration of action of these deltamethrin formulations against susceptible laboratory-reared and wild, free-flying Aedes aegypti and Ae. albopictus. Analyses of bioassay results showed that deltamethrin SC-PE 30 mg/m(2) has improved longevity in comparison to deltamethrin WG 30 mg/m(2). Deltamethrin SC-PE 30 mg/m(2) was effective until week 17 (producing > 80% mortality), surpassing deltamethrin WG 30 mg/m(2) which only lasted until week 10. This was supported by post-hoc test analyses which demonstrated that deltamethrin SC-PE 30 mg/m(2) produced the highest mean of mortality in laboratory-reared Aedes species and the wild Ae. albopictus. However, the effective duration of action of deltamethrin SC-PE (17 weeks) was less than the recommended period by WHO (6 months) but was reasonable given that the spraying was undertaken outdoor. This preliminary data could be of use for the deployment of locally adapted ORS operation in controlling dengue.